The Spanish presidency and its influence on EU-Latin American relations - Naab, Anna (2010)
Abstract: "In the last years the EU has been focusing primarily on internal affairs, such as the quarrel over a new treaty. Foreign affairs have been dominated mostly by the European Neighborhood Policy and political and economic relationships with the immediate neighbors by land and sea have been strengthened.The Spanish takeover of the Presidency of the Council of the European Union on January 1st, 2010, however,might herald changes in this respect. First of all,the introduction of the Lisbon Treaty,whose implementation the Spanish presidency has strongly committed itself to, will end years of struggling for an appropriate political and institutional setting and hopefully bring about various improvements. Secondly, the Spanish presidency has also announced it will pay more attention to other regions,first and foremost the region with which Spain has close economic, cultural and linguistic ties, i.e. Latin America." (author's abstract)